City integrated marketing communication – identification and measurement framework - Daszkiewicz, Magdalena; Mazurek, Edyta; Pukas, Anetta (Publishing House of Wroclaw University of Economics and Business, 2023)
New challenges resulting from dynamic changes observed in the twenty-first century are driving the evolution of approaches to city marketing communication. This article adapts the integrated marketing communication (IMC) concept for cities and develops a measurement framework and a theoretically consistent, valid, and reliable measurement tool for assessing city integrated marketing communication (CIMC). A literature review and previous qualitative studies provided the basis for conceptualising and identifying the specific constructs of CIMC, namely strategic consistency, interactivity, and stakeholder-centred focus. The research developed a theoretically consistent, valid, and reliable measurement tool for assessing CIMC. Empirical validation of the CIMC scale was conducted on data collected from a survey completed by representatives of municipal offices responsible for marketing communication in 279 Polish cities. The value and originality of this article derive from the development of the measurement framework and the new scale for assessing CIMC, which provide the foundation for further research on model solutions in this area. The measurement tool also contains subscales that can be used in research on specific dimensions of city marketing communication. The CIMC scale will assist practitioners in their decision-making processes and facilitate comparisons of cities in a local and international context.
Argumenta Oeconomica, 2023, Nr 1 (50), s. 5-32
Keywords: city integrated marketing communication; city marketing; integrated marketing communication; place marketing; measurement framework; scale development